The Comparison of the Legal Knowledge, Elder Abuse Prevention Attitude and Behavior of Professional and Practical Nurses at Police General Hospital - Keskomon, Thipkhumporn; Thawitsri, Nuanla-or; Khiaosalap, Sunaree; Lapjit, Wassana; Vivekram, Thanyathorn; Senakun, Arrawadee; Suksab, Wilasinee; Siri, Sriyapak (Journal of The Royal Thai Army Nurses, 2021)
The objectives of this descriptive research were to study and compare the legal knowledge, attitude towards elder abuse prevention, and elder abuse prevention behavior of professional and practical nurses. The samples with simple random sampling were 88 professional nurses and 84 practical nurses. The instruments consisted of test items about legal knowledge, the scale of attitude towards elderly abuse prevention, and the questionnaire of the elderly abuse prevention behavior. The indices of item objective congruence (IOC) of all instruments equal to 1.00. Kuder-Richardson reliability coefficient of test was 0.49 and the Cronbach alpha reliability coefficients were 0.79 and 0.80, respectively. Data were analyzed using descriptive statistics: frequency, percentage, arithmetic mean, standard deviation, and independent t-test. The results were as follows: 1) Professional and practical nurses had the legal knowledge scores above 60%, but these scores had no statistical difference between them at the .05 level; 2) Both groups had the positive attitude towards elder abuse prevention and the high level of elder abuse prevention behavior; 3) Practical nurses had statistically significant and higher attitude and behavior scores than professional nurses at the .05 level. Nursing institutions should review the nursing curriculum and nursing administrators should review organizational cultures about the report of colleagues’ inappropriate behaviors and encourage ethical courage for elder violence prevention in the workplace and families.